2019
DOI: 10.4300/jgme-d-18-00601.2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Entrustable Professional Activities Using an Orientation OSCE: Identifying the Gaps

Abstract: Background A residency program's intern cohort is comprised of individuals from different medical schools that place varying levels of emphasis on Core Entrustable Professional Activities for Entering Residency (CEPAERs). Program directors have expressed concerns about the preparedness of medical school graduates. Though guiding principles for implementation of the CEPAERs have been published, studies using this framework to assess interns' baseline skills during orientation are limited.Objective A CEPAER-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…In a study, 89% of interns claimed that they would make a change according to EPAs feedback in their next consultation request[ 28 ]. Similar evidence is provided by two other studies: in the first one, participants agreed that EPAs met the defined criteria and were considered important for graduates to be able to demonstrate the expected behaviors[ 32 ]; in the second one, the majority of the physicians agreed that the assessment based on EPAs was meaningful, and immediate feedback was beneficial[ 15 ]. Another 3-year longitudinal study claims that EPAs serve as an effective channel for communicating expectations to resident participants[ 20 ].…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…In a study, 89% of interns claimed that they would make a change according to EPAs feedback in their next consultation request[ 28 ]. Similar evidence is provided by two other studies: in the first one, participants agreed that EPAs met the defined criteria and were considered important for graduates to be able to demonstrate the expected behaviors[ 32 ]; in the second one, the majority of the physicians agreed that the assessment based on EPAs was meaningful, and immediate feedback was beneficial[ 15 ]. Another 3-year longitudinal study claims that EPAs serve as an effective channel for communicating expectations to resident participants[ 20 ].…”
Section: Resultsmentioning
confidence: 55%
“…Compared with previous 7 year[ 9 ], the proportion of teaching sessions in programs risen from 17% to 24.1%, while the ratio of curriculums decreased from 33% to 17.2%, shown a tendency that more and more EPAs being implemented or assessed directly rather than insert into curriculums. Besides, two studies attempt to assess participants’ EPA levels by implementing objective structured clinical examination (OSCE) [ 14 , 15 ], which provide a new prospective for combining EPAs with existing assessment frameworks.
Figure 2.
…”
Section: Resultsmentioning
confidence: 99%
“…Ethical Approval The University of Pittsburgh Institutional Review Board (IRB #2003005) determined that this study is exempt. Depression/anxiety 1 (1) n, number of interns who circled this response. Interns were asked to circle three topics they felt were most important…”
Section: Compliance With Ethical Standardsmentioning
confidence: 99%
“…Several studies suggest that incoming interns lack clinical and professional skills that residency program directors expect interns to have mastered during medical school [1][2][3][4][5]. Over the last decade, medical educators have created residency preparatory courses (boot camps) to bolster the skills of fourth-year medical students (MS4s) about to enter residency.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that CPAs using SPs, such as the OSCE, are reliable and valid to evaluate the clinical performance of healthcare students, and allow examiners to provide more accurate feedback to students [28][29][30][31][32][33][34]. However, an issue for CPAs is the possible subjectivity of examiners that may introduce the risk of unfairness and bias, especially when examiners are affected by construct-irrelevant characteristics, such as ethnicity and/or gender [3,[35][36][37].…”
Section: Objective Structured Clinical Examination (Osce)mentioning
confidence: 99%